Analyzing the Sustainability Report of Multinational Companies: Using HP as an Example - Chai, Yuhan (International Journal of Global Economics and Management, 2024)
Nowadays, more and more multinational corporations attach importance to sustainable development, and most of them present their annual decisions in sustainability reports. However, most multinational corporations only execute sustainability decisions to establish a good corporate image and reputation and meet public expectations, without rigorously evaluating the feasibility of sustainability reports and subsequent measurements, so this article uses HP, a representative multinational corporation, and critically analyzes HP’s sustainability reports in recent years using the well-known and widely used GRI framework and corporate social responsibility theory.